EKSPRESI TEKSTUAL TEKS EKSPOSISI DALAM BUKU BAHASA INDONESIA KELAS X SMA KURIKULUM 2013 TERBITAN KEMDIKBUD TAHUN 2015 - Yusuf, Munawwar; Talib, Jihad (LPPM Universitas Muhammadiyah Bulukumba, 2025)
This study aims to describe textual expressions in the form of theme–rheme relations in exposition texts contained in the Indonesian Language Student Book for Grade X Senior High School published by the Ministry of Education and Culture in 2015. This research employed a descriptive qualitative method with data sources in the form of clauses from the exposition texts. Data were collected through observation and reading techniques, then analyzed by identifying the theme–rheme structure in each clause based on Halliday’s Systemic Functional Linguistics (SFL) framework. The results show that exposition texts in the student book are dominated by topical themes in the form of nouns (e.g., drugs, earth, problems, series of events), which serve as the starting point of discourse in presenting factual issues. In addition, textual themes (e.g., however, or alternatively) and adverbial themes (e.g., nowadays, not a few) were also found, which play a role in providing emphasis, marking transitions, and strengthening evaluations. These theme–rheme patterns contribute to discourse cohesion as well as systematic argumentative strategies in exposition texts.